Community Empowerment of Micro, Small, and Medium Enterprises (MSMEs) in Ngamprah District, West Bandung Regency - Sudrajat, Fahmi Saeful Bahri; Kurniati, Poni Sukaesih (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in promoting regional economic growth and improving community welfare. However, MSME empowerment at the sub-district level still faces challenges, including limited human resource capacity, restricted access to capital, and weak market access. This study aims to analyze MSME empowerment strategies and the role of the local government in Ngamprah District, West Bandung Regency. This research uses a qualitative descriptive method, drawing on secondary data from scientific journals, government documents, and relevant official publications. The findings show that empowerment strategies include capacity building through training programs, facilitating access to capital, and strengthening market access through digital technology. The local government acts as a facilitator, regulator, and catalyst in supporting MSME sustainability. Integrated, sustainable strategies are necessary to ensure effective, targeted empowerment programs.